2022
DOI: 10.1111/nph.18668
|View full text |Cite
|
Sign up to set email alerts
|

MUS81 is required for atypical recombination intermediate resolution but not crossover designation in rice

Abstract: Summary The endonuclease methyl methanesulfonate and UV‐sensitive protein 81 (MUS81) has been reported to participate in DNA repair during mitosis and meiosis. However, the exact meiotic function of MUS81 in rice remains unclear. Here, we use a combination of physiological, cytological, and genetic approaches to provide evidence that MUS81 functions in atypical recombination intermediate resolution rather than crossover designation in rice. Cytological and genetic analysis revealed that the total chiasma num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In rice, GEN1, the homolog of the Holliday junction resolvase is necessary for class II CO formation (Wang et al, 2017) while it is not in Arabidopsis (Bauknecht and Kobbe, 2014;Olivier et al, 2016), suggesting that the MUS81 pathways have diverged between dicots and monocots. Compared to Arabidopsis, the MUS81 pathway contributes even less to CO designation in rice (Wang et al, 2017;Mu et al, 2022), suggesting that the weight of the different pathways described in this review probably depend on each species.…”
Section: An Integrated Molecular Model For Co Formation In Plantsmentioning
confidence: 89%
See 1 more Smart Citation
“…In rice, GEN1, the homolog of the Holliday junction resolvase is necessary for class II CO formation (Wang et al, 2017) while it is not in Arabidopsis (Bauknecht and Kobbe, 2014;Olivier et al, 2016), suggesting that the MUS81 pathways have diverged between dicots and monocots. Compared to Arabidopsis, the MUS81 pathway contributes even less to CO designation in rice (Wang et al, 2017;Mu et al, 2022), suggesting that the weight of the different pathways described in this review probably depend on each species.…”
Section: An Integrated Molecular Model For Co Formation In Plantsmentioning
confidence: 89%
“…It has been proposed that these dissolution pathways leading to NCO could be especially important for multi-invasion complexes formed between more than two DNA molecules that would otherwise lead to aberrant recombination intermediates (Emmenecker et al, 2022;Mu et al, 2022). Whether or not these pathways could be involved in a putative chromatid interference phenomenon (Zhao et al, 1995;Sarens et al, 2021) is still unknown.…”
Section: An Integrated Molecular Model For Co Formation In Plantsmentioning
confidence: 99%
“…FIGL1 is, however, essential for meiotic DSB repair in different crop plants, including rice figl1 mutant showing chromosome fragmentation at metaphase I (64, 66). These unrepaired breaks might result from complex DMC1-and RAD51-mediated interhomolog invasions, which MUS81 is unable to repair, given a more considerable genome complexity and chromosome number in rice (74). Our data provide evidence that the RAD51-dependent pathway promotes accurate meiotic repair outcomes in Arabidopsis figl1 .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that rice msh4 has the least residual chiasmata frequent among zmm mutants and the distribution of residual chiasmata is consistent with a Poissonpredicted distribution (Mu et al, 2023;Zhang et al, 2014). To further confirm rice fancm limits class II crossovers, we counted the distribution of chiasmata present in the fancm msh4 double mutant using previously described criteria (Sanchez Moran et al, 2001).…”
Section: Fancm Suppresses Class II Crossoversmentioning
confidence: 99%